2010
DOI: 10.1097/ncn.0b013e3181d783e5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Midcurricular Examination for Identifying At-Risk Nursing Students

Abstract: The purpose of this study was to investigate the usefulness of the Health Education Systems, Inc, midcurricular examination in identifying at-risk students earlier in their nursing career. This study used quantitative measures to examine the relationship between the Health Education Systems, Inc, midcurricular examination and the students' success in the nursing program and their performance on the HESI exit examination and the NCLEX-RN. Statistically significant correlations were found between the score attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…During the same time frame, five researchers reported on the predictive accuracy of HESI examinations. In a study by Gilmore (2008) nursing GPA was the only independent predictor of NCLEX success in that study [24]. Uyehara (2007) found when all variables are analyzed; the scores on the NLN Adult Health Comprehensive Test were significant predictors (p < 0.0001) [27].…”
Section: Predictive Studiesmentioning
confidence: 84%
See 2 more Smart Citations
“…During the same time frame, five researchers reported on the predictive accuracy of HESI examinations. In a study by Gilmore (2008) nursing GPA was the only independent predictor of NCLEX success in that study [24]. Uyehara (2007) found when all variables are analyzed; the scores on the NLN Adult Health Comprehensive Test were significant predictors (p < 0.0001) [27].…”
Section: Predictive Studiesmentioning
confidence: 84%
“…Findings from the study suggest that subtle differences in test scores could be used to identify students at-risk for failing the NCLEX-RN ® [24]. There was one report of findings that did not support predictive accuracy of the HESI.…”
Section: Predictive Studiesmentioning
confidence: 85%
See 1 more Smart Citation
“…This, in turn, is a good predictor of at-risk students early in their curricular progression. 9 Studies have also shown entering GPA, academic success in the program, 10,11 and the HESI exit exam provide predictive evidence in nursing student success. 12 The American Board of Anesthesiology/American Society of Anesthesiologists uses the In-Training Examination (ITE) predictor test for medical residents, and it accounts for approximately half of the variance of the Part I of the licensure exam.…”
Section: Introductionmentioning
confidence: 99%